Comparison of multimodal analgesia with thoracic epidural after transthoracic oesophagectomy. Issue 1 (13th December 2020) - Ng Cheong Chung, J; Kamarajah, S K; Mohammed, A A; Sinclair, R C F; Saunders, D; Navidi, M; Immanuel, A; Phillips, A W
Abstract : Thoracic epidural is the most commonly used analgesia immediately after oesophagectomy. It may cause hypotension and inhibit mobilization. Multimodal analgesia provides comparable pain control with less impact on blood pressure. Abstract: Background: Thoracic epidural analgesia (TEA) has been regarded as the standard of care after oesophagectomy for pain control, but has several side-effects. Multimodal (intrathecal diamorphine, paravertebral and rectus sheath catheters) analgesia (MA) may facilitate postoperative mobilization by reducing hypotensive episodes and the need for vasopressors, but uncertainty exists about whether it provides comparable analgesia. This study aimed to determine whether MA provides comparable analgesia to TEA following transthoracic oesophagectomy. Methods: Consecutive patients undergoing oesophagectomy for cancer between January 2015 and December 2018 were grouped according to postoperative analgesia regimen. Propensity score matching (PSM) was used to account for treatment selection bias. Pain scores at rest and on movement, graded from 0 to 10, were used. The incidence of hypotensive episodes and the requirement for vasopressors were evaluated. Results: The study included 293 patients; 142 (48.5 per cent) received TEA and 151 (51.5 per cent) MA. After PSM, 100 patients remained in each group. Mean pain scores were significantly higher at rest in the MA group (day 1: 1.5 versus 0.8 in the TEA group, P  = 0.017; day 2: 1.7 versus 0.9 respectively, P  = 0.014; day 3: 1.2 versus 0.6, P  = 0.047). Fewer patients receiving MA had a hypotensive episode (25 per cent versus 45 per cent in the TEA group; P  = 0.003) and fewer required vasopressors (36 versus 53 per cent respectively; P  = 0.016). There was no significant difference in the overall complication rate (71.0 versus 61.0 per cent; P  = 0.136). Conclusion: MA is less effective than TEA at controlling pain, but this difference may not be clinically significant. However, fewer patients experienced hypotension or required vasopressor support with MA; this may be beneficial within an enhanced recovery programme.